Existence results for positive solutions of a fractional boundary value problem involving a perturbation term (Letters in Nonlinear Analysis and its Applications, 2024)
A new fixed-point result criteria for the existence of positive solutions to the considered problem are established based on upper and lower estimates and \(α\)-admissible mappings in \(F\)-metric spaces for Green's function related to a fractional boundary value problem with a perturbation term, which has been derived.
Keywords: Fractional differential equations; admissible mappings; perturbation term; ower positive solution; F -metric spaces